Alumni Live Culture - Gargallo, M. Àngels Morant; Carpena, Aránzazu Gimeno (ICAReAlumni Conference Proceedings, 2020)
Alumni Live Culture was born with the goal of making our alumni's work and projects known in the fields of cinema, music, photography, writing and art (in any of its formats) and offer spaces to allow opportunities for collaboration between them to emerge. This is a way to strengthen the network of former students and their sense of belonging to the Universitat Jaume I. Alumni Live Culture is carried out on YouTube, combining the new contents on YouTube with YouTube Live.